Notes on a small collection of Prioninae from North-East Madagascar with the description of a new Schizodontus Quentin & Villiers, 1974 (Cerambycidae, Closterini) - Bouyer, Thierry; Drumont, Alain; Roland, Lily-Arison Rene De; Slootmaekers, Dan; Pirkl, Jiri; Mittermeier, John C; Wright, Dale R; Jocque, Merlijn (Zootaxa, 2021)
We present observations from a small collection of longhorns belonging to the subfamily Prioninae and collected during an expedition in the rainy season to a newly designated protected area, Mahimborondro, in North-East Madagascar. The material includes a new species (S. mahimborondroensis sp. nov.) of Closterini (Prioninae) from a small genus with only two described species (Schizodontus angustus Quentin & Villiers, 1974 and S. latus Quentin & Villiers, 1974). An identification key to the three species is included.